Gap Analysis between Indian Institutes and their Counterparts Abroad - Naik, B. M.; Kandlikar, W. S. (Journal of Engineering Education Transformations, 2008)
Where does India stand in the world list in higher education? Why thousands of students every year go abroad for advanced learning? What do they teach which we do not? How are their institutes different from Indian? Where do we go wrong? We have too much of rote learning. They have more of innovation, creativity. All teachers abroad hold doctorate degree. where as in India very few. Why coaching industry in India is booming? Nalanda and Taxshila were the first universities of the world, where scholars used to come from abroad. Now why a shift in culture has taken place and students going abroad? It is essential at this juncture of time to make introspection and learn from the world experience in science and engineering education. and derive lessons. The future of youths depends on knowledge rather than the resources. Status of India in world. in leadership. income level. and well being of people depends on its scientific and technological capability. India. to cope with challenges will have to enlarge the scope of institutions to cover research. innovation. creativity. generation of theories. technology creation, patent and IPR, creation of New Technology Based firms etc. What value we attach to above in budgeting? Students studying today in universities are tomorrow s leaders. in politics, industry. academics etc. They sit in parliament, board room, write books. become creative thinkers. and drive the society to progress. For India to win in world economy they have to be competitive by world standards. They have to learn not only known knowledge but learn to discover unknown. Remember! To be able to have world class leaders tomorrow we have to have today world class professors and world class institutes. The article presents in brief, the gap analysis in respect of visions and missions; policies and practices; organization structures, systems and procedures in India and their counterpart institutions in developed countries. They are critical to the success. IITs were set up under foreign collaboration. Their visions, missions, policies and practices are molded on global lines. Hence they could shine. The paper observes that rest of the Indian higher education is far too behind. India will have to capitalize on emerging technology to fulfill people s needs. Institutions will have to have wellsprings of new knowledge like in developed countries and not remain mere reflection centers. The gap analysis presented here makes an attempt to find answers to the questions raised above.